2018
DOI: 10.1055/s-0038-1675592
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Quality of Life Outcomes After Extended Endonasal Approaches to the Skull Base

Abstract: Introduction Endoscopic endonasal skull base surgery (EESBS) leads to significant alterations in sinonasal anatomy and physiology. However, there is limited data available on quality of life (QOL) outcomes following EESBS. Methods A retrospective review of patients undergoing EESBS from January 2014 to April 2017 was performed. Records were reviewed for clinical history, operative details, and 22-item Sinonasal Outcomes Test (SNOT-22) scores. Unadjusted and adjusted linear regression models were ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…studies reporting sinonasal outcomes beyond 3 months of surgery do not document any significant further worsening of QoL. 16,28,37,47 Previous Studies on Sinonasal Quality of Life…”
Section: Assessing Sinonasal Outcomementioning
confidence: 98%
See 3 more Smart Citations
“…studies reporting sinonasal outcomes beyond 3 months of surgery do not document any significant further worsening of QoL. 16,28,37,47 Previous Studies on Sinonasal Quality of Life…”
Section: Assessing Sinonasal Outcomementioning
confidence: 98%
“…Postoperative follow-up at 3-6 months was chosen in the present study as it has been shown to be adequate to achieve complete healing of the nasal cavities and most studies reporting sinonasal outcomes beyond 3 months of surgery do not document any significant further worsening of QoL. 16,28,37,47 Previous studies on sinonasal quality of life Bhenswala et al 48 in a meta-analysis of sinonasal quality of life outcomes after endoscopic endonasal skull base surgery using SNOT-22, demonstrated a temporary worsening of sinonasal QoL at ≤ 4 weeks after surgery in all patients but they returned to their preoperative sinonasal status within 3 months. In patients with impaired preoperative sinonasal QoL, they demonstrated a continued improvement beyond the baseline after 3 months reaching a peak at 1 year postoperatively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Although validated as an outcomes assessment tool specifically for chronic rhinosinusitis (CRS), the SNOT-22 has also been used to assess QOL outcomes in patients undergoing septoplasty, 10 rhinoplasty, 11 and even EESBS for skull base tumors. 12,13 However, no study has evaluated SNOT-22 QOL scores in patients undergoing surgical repair for spontaneous CSF rhinorrhea.…”
Section: Introductionmentioning
confidence: 99%